2009
DOI: 10.1111/j.1440-1746.2009.05979.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 3′‐end variable region of the cagA gene in Helicobacter pylori isolated from Iranian population

Abstract: Background and Aims-The 3′ region of the cagA gene, the most well-known virulence factor of Helicobacter pylori, contains Glu-Pro-Ile-Tyr-Ala (EPIYA) motifs. Four segments flanking the EPIYA motifs, EPIYA-A, -B, -C, or -D, were reported to play important roles in H. pylori-related gastroduodenal pathogenesis. The aim was to determine the roles of EPIYA segments in gastroduodenal pathogenesis in an Iranian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
5
22
0
Order By: Relevance
“…In contrast, Batista et al (2011) and Torres et al (2012) did not find any association between ulcers and the number of EPIYA-C repeats. Acosta et al (2010) and Shokrzadeh et al (2010) could not find differences between EPIYA patterns and clinical outcomes. The number of EPIYA-C with multiple repeats was observed less frequently in cases with gastritis (CG) and DU cases (PG).…”
Section: Epiya-c and -D Have A Role In The Interaction Betweenmentioning
confidence: 90%
“…In contrast, Batista et al (2011) and Torres et al (2012) did not find any association between ulcers and the number of EPIYA-C repeats. Acosta et al (2010) and Shokrzadeh et al (2010) could not find differences between EPIYA patterns and clinical outcomes. The number of EPIYA-C with multiple repeats was observed less frequently in cases with gastritis (CG) and DU cases (PG).…”
Section: Epiya-c and -D Have A Role In The Interaction Betweenmentioning
confidence: 90%
“…Our results represented more conserved pathogenicity locus in severe gastritis patients, even among the strains with lower repeats of EPIYA motif. However, involvement of other H. pylori virulence factors or host factors also seems probable (25,(57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the previous studies performed on adults, controversial results have been obtained in Iran. While a great number of studies in Iran indicated no influence of cagA status or its 3' variable region on the progression of disease (26)(27)(28)(29)(30)(31)(32)(33)(34), correlation between positive cagA status and severe clinical outcomes was reported in some other studies (35)(36)(37). Consistent with the cases of Iranian adult populations (27,28,(38)(39)(40)(41), vacA s1 was the most prevalent in the present investigation (Table 3).…”
Section: Discussionmentioning
confidence: 99%